THE FACTOR OF SPEAKING PROBLEMS FACED BY THE ELEVENTH GRADERS OF SMA NEGERI 1 TANJUNG SELOR - Juliyati, Patri; Winarno, Winarno; Arifin, Arifin; Widhianty, Devy (Universitas Borneo Tarakan, 2022)
The purpose of the research was to describe the results of the speaking problem factors of class XI students at SMA Negeri 1 Tanjung Selor. The design of the research was a descriptive. The subject was taken by random sampling technique. The researcher took 28 students of class XI with each representative from 8 classes. To collect the data, the researcher used documentation, questionnaire, and interview. Based on the results of the questionnaire showed that 1) there were 53.6% of students answered the lack of proper vocabulary selection, 2) 42.9% of students answered less confident in pronunciation, 3) 35.7% of students answered that they did not use proper grammar, and 46.4% of students answered that they could not speak English well. The results of interview with the teacher of English and the students showed that there were several problems faced by the students namely weak of grammar, weak of pronunciation in English, not fluent in speaking English, lack of vocabulary, difficulty compiling English sentences, lack of practice speaking at home and at school, embarrassed by wrong pronunciation and fear of being laughed at by friends. Based on the result of the research showed there were some factor of speaking problems faced by the eleventh graders of SMA Negeri 1 Tanjung Selor namely less of confidence, weak of grammar, weak of pronunciation in English, not fluent in speaking English, lack of vocabulary, difficulty compiling English sentences, lack of practice speaking.